2020
DOI: 10.5005/jp-journals-10024-2759
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants on the Shear Bond Strength of Orthodontic Brackets Bonded to Bleached Human Teeth: An In Vitro Study

Abstract: Aim:The aim of this study was to evaluate the effects of different concentrations of sodium ascorbate (SA), green tea (GT), and chamomile (CM) on the shear bond strength (SBS) of metal orthodontic brackets bonded to teeth bleached with 40% hydrogen peroxide (HP). Materials and methods: Ninety-four sound premolars were divided into eight groups: group I (control + no bleaching), group II (bleaching + immediate bonding), group III (bleaching + 10% SA), group IV (bleaching + 35% SA), group V (bleaching + 0.5% GT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 32 publications
0
16
0
2
Order By: Relevance
“…High concentration of hydrogen peroxide used in in-office bleaching can decrease the efficacy of sodium ascorbate in reversing the bond strength. [ 11 ] Studies that have reported the optimal efficacy of sodium ascorbate in increasing the bond strength after bleaching have used low-concentration carbamide peroxide as the bleaching agent. [ 3 11 24 27 28 29 30 ] Since hydrogen peroxide generates higher amounts of free radicals than carbamide peroxide, sodium ascorbate may be more effective in reversing the reduction in bond strength caused by carbamide peroxide rather than hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High concentration of hydrogen peroxide used in in-office bleaching can decrease the efficacy of sodium ascorbate in reversing the bond strength. [ 11 ] Studies that have reported the optimal efficacy of sodium ascorbate in increasing the bond strength after bleaching have used low-concentration carbamide peroxide as the bleaching agent. [ 3 11 24 27 28 29 30 ] Since hydrogen peroxide generates higher amounts of free radicals than carbamide peroxide, sodium ascorbate may be more effective in reversing the reduction in bond strength caused by carbamide peroxide rather than hydrogen peroxide.…”
Section: Discussionmentioning
confidence: 99%
“…[ 11 ] Studies that have reported the optimal efficacy of sodium ascorbate in increasing the bond strength after bleaching have used low-concentration carbamide peroxide as the bleaching agent. [ 3 11 24 27 28 29 30 ] Since hydrogen peroxide generates higher amounts of free radicals than carbamide peroxide, sodium ascorbate may be more effective in reversing the reduction in bond strength caused by carbamide peroxide rather than hydrogen peroxide. [ 11 31 32 ] In the present study, 40% hydrogen peroxide was used, which produces free radicals 10 times more than carbamide peroxide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plants, tea and green tea contain natural polyphenols, which have several functions in the oral cavity, such as bacterial control and antioxidation, and have recently been employed as “processing cofactors” to improve the mechanical and functional properties of biomaterials [ 32 ]. Previous studies have used tea or green tea to reverse the SBS between adhesives and bleached enamel, with antioxidants being capable of neutralizing free radicals produced by bleaching treatment [ 33 , 34 ]. Epigallocatechin gallate is one of the most important polyphenols used in dental applications (EGCG).…”
Section: Discussionmentioning
confidence: 99%
“…Most advanced studies evaluate the effects of different concentrations of sodium ascorbate (SA), green tea (GT), and chamomile (CM) on the shear bond strength (SBS) of metal orthodontic brackets bonded to teeth bleached with 40% hydrogen peroxide (HP). Results showed that bond strength can be enhanced by using 0.5% or 1% GT or 0.5% CM to allow bracket bonding immediately after bleaching [11] Recent studies have emphasized that in addition to the microbial activity, the host immuneinflammatory reactions destroy the oral tissues to a greater extent [12]. In such cases, green tea is considered to be a natural preventive and curative agent.…”
Section: Introductionmentioning
confidence: 99%